Posterior Reversible Leukoencephalopathy Syndrome After Kratom Ingestion. Issue 3 (1st July 2017) - Castillo, Austin; Payne, J. Drew; Nugent, Kenneth
Abstract : Posterior reversible encephalopathy syndrome has been associated with hypertension, preeclampsia, cancer chemotherapy, and drugs of abuse, such as amphetamine and methamphetamine. We report a young man who suddenly developed severe headache, disorientation, and aphasia following ingestion of kratom and Adderall. Computed tomography and magnetic resonance imaging of his head revealed foci of vasogenic edema in the posterior occipital lobes, frontal lobes, and brainstem. In addition, he had a small area of hemorrhage in the left posterior occipital lobe. Lumbar puncture revealed an increased number of red blood cells but no other abnormalities. His initial blood pressure was elevated but returned to normal during hospitalization. This case suggests that kratom can cause posterior reversible encephalopathy syndrome and needs to be considered when patients present to emergency centers with headaches, confusion, and visual disturbances.